1999
DOI: 10.1002/(sici)1521-396x(199909)175:1<437::aid-pssa437>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of ZnSe Crystals Subjected to Laser Irradiation

Abstract: An influence of power laser pulses of subthreshold intensity with hν < Eg on the defect structure, surface states and optical properties has been studied in high‐resistivity, undoped, cubic ZnSe single crystals with different degrees of purity. The laser‐stimulated modification of the spectra of photoconductivity, photoluminescence, Raman scattering and optical absorption was due to laser‐induced formation of intrinsic point defects of structure in the bulk as well as, particularly, in the surface layer of irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Based on our investigations of the spectra of photoluminescence, Raman scattering and optical absorption in high-resistivity, undoped ZnSe crystals with different degree of purity, subjected to pulsed laser irradiation [8,9] it may be concluded that laser-stimulated photosensitization of ZnSe crystals was attributed primarily to modification of a system of intrinsic point defects. A reduction in the photoluminescence bands at 300 K and 77 K, which were due to a free hole-donor transition and annihilation of free excitons, respectively, the appearance of the additional peaks and increase in the background in the Raman spectra [9] as well as an increase in the optical absorption in the transparency range of ZnSe [8] suggest an increase in the number of intrinsic point defects of the structure in the crystals after laser irradiation. The observed rise of the slow component of the photocurrent pulse of the laserphotosensitized ZnSe crystals can be explained by an increase in the electron lifetime or by a gain in the occupancy of the slow recombination centres S 1 with electrons, that is to say, the probability of the transitions of electrons from these centres to a conduction band is enhanced [13].…”
Section: Study Of the Photosensitization Phenomenon In Undoped Znse C...mentioning
confidence: 94%
See 2 more Smart Citations
“…Based on our investigations of the spectra of photoluminescence, Raman scattering and optical absorption in high-resistivity, undoped ZnSe crystals with different degree of purity, subjected to pulsed laser irradiation [8,9] it may be concluded that laser-stimulated photosensitization of ZnSe crystals was attributed primarily to modification of a system of intrinsic point defects. A reduction in the photoluminescence bands at 300 K and 77 K, which were due to a free hole-donor transition and annihilation of free excitons, respectively, the appearance of the additional peaks and increase in the background in the Raman spectra [9] as well as an increase in the optical absorption in the transparency range of ZnSe [8] suggest an increase in the number of intrinsic point defects of the structure in the crystals after laser irradiation. The observed rise of the slow component of the photocurrent pulse of the laserphotosensitized ZnSe crystals can be explained by an increase in the electron lifetime or by a gain in the occupancy of the slow recombination centres S 1 with electrons, that is to say, the probability of the transitions of electrons from these centres to a conduction band is enhanced [13].…”
Section: Study Of the Photosensitization Phenomenon In Undoped Znse C...mentioning
confidence: 94%
“…The LACs were obtained from measurements of the amplitude A of the photocurrent pulses (curves 1, 3) and the amplitude A s of the slow (longtime) component of the decay of the photocurrent signal (photoconductivity relaxation curve) which determined the curve 1 (curve 2). Reasoning from the presumption that the carrier mobility did not vary significantly with illumination [5][6][7][8][9][10][11][12], the amplitudes A and A s were considered to be proportional to the concentration n of the nonequilibrium charge carriers [13]. At low excitation rates the LAC was linear with the slope 1 (curves 1), indicating impurity generation of carriers and their linear recombination.…”
Section: Study Of the Pulsed Photoconductivity Of Undoped Znse Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc selenide (ZnSe) is a II-VI intrinsic semiconductor, widely studied owing to its familiar zinc blende structure, extremely wide-bandwidth transmittance, and a high-energy room-temperature bandgap of 2.7 eV. [1][2][3][4][5] Its applications include blue LED and infrared optics; with possible future commercial implementation in digital displays, data storage, and even biomedical imaging. [1][2][3] Quite recently, research works on the optical properties of ZnSe include photoemission and lasing action via single-photon or two-photon excitation.…”
Section: Introductionmentioning
confidence: 99%